Improvement of Mathematics Learning Outcomes of Circle Materials Through the Discovery Learning Model in Madrasah Ibtida'iyah - Sa'diyah, Halimatus (FITK UIN Walisongo Semarang, 2024)
Discovery Learning is a teaching method in which teachers design a learning process so that students can discover new knowledge independently without prior notice from the teacher. This study aims to evaluate the application of the Discovery Learning model in improving mathematics learning outcomes, especially circle material, in grade VI MI NU Ma'rifatul Ulum 02 Kudus students in 2022. The research method used is Classroom Action Research (PTK) with three cycles, adopting the design of the PTK model of Stephen Kemmis and Robin McTaggart which involves the following steps: (1) planning, (2) implementation of actions, (3) observation, and (4) reflection. The results show that the application of Discovery Learning has succeeded in achieving the expected success indicators. From the data analysis, the completeness of student learning outcomes increased significantly: in the first cycle it reached 70%, in the second cycle it increased to 80%, and in the third cycle it reached 90%. This improvement shows that the Discovery Learning model is effective in improving student learning outcomes in circle materials